FEATURES OF PREPOSITIONAL CONSTRUCTIONS AND THEIR MEANINGS IN THE CONTEXT - Jumanazarov Samandar Urinovich (European Science Publishing, 2024)
English-based prepositions combined with verbs have the ability to pronounce procedural, continuous meanings in the adverbial spelling function. The potential analysis of the English prepositions indicates that their meanings are not only lexical, but also their ability to use these prepositions, their grammatical functions, and their importance in the English language and spelling is observed. The article presents theoretical ideas in this regard and proves them with examples.
Keywords: Manuscripts; prototype; superficial; combination; compounds; phraseological; predicament; predetermined; manifestations.